Economic and Health Hazards of Women Fish Vendors in Chennai District of Tamil Nadu, India - Jaheer Mukthar KP; Dr. Raju.V; Dr Sivasubramanian K (Training & Research Institute - Jeramba Ilmu Sukses, 2021)
The women constitute 48.1 percent of the total population in India. (CIA, 2020). The women pay vital place within the fisheries societies, that they are often invisible unsupported or not recognized. In the economic activities of fisheries, women are mostly engaged in post-harvest of fishes among the marine fisher communities in India. Because, the women constitute nearly 75 percentage of fish marketing and selling activities. The women are the primary troupes in processing of fish, marketing and selling to the ultimate consumers and contributing a sizable income to the family. (ICSF, 1997). But the women workforce has not yet recognized fully. The women fish vendors work as a pivotal role in between the fisherman and consumers in an intangible way in the urban area. Fish selling or vending is a non-conventional form of occupation and it is main kind of livelihood mass population in many Indian states. The women contribute an important function in fisheries especially the post-harvest of fishes, i.e marketing and selling of fishes. According to the marine fisheries census (2005), reveals that the whole marine fishier populace of 9 seaside states and the union territories in India is around 3519116. To carry out the research study, the researcher is followed the empirical research method. The empirical research study is uses to prove the instances through the empirical relevance. The present study aims to prove the socio-economic implications of the women fish vendors through the direct field survey. So that the empirical method of research type is more appropriate and apt for this research work. The main idea of applying this research method to gain the knowledge through direct method of observation and experience. The average income of the respondent is calculated as 6111.11 per month. The minimum income per month is recorded as rupees 4000 and the maximum recorded as rupees 9000. Average investment level of the women fish vendor is registered as rupees 2611.111 per day with the minimum amount of rupees 1500 and the maximum amount of rupees 4000. Almost all the respondents are suffering from occupational health issues. The mean amount of savings per month of women fish vendors have recorded as 266.667 with the minimum of zero savings and the maximum of 500 rupees per month. The average borrowings of the respondent were rupees 7848.485 per month. On the whole, the women fish vendors are economically poor vulnerable section in the society.